Über die Hyperflächen des metrischen Raumes von Hyperebenenelementen - Medviedevaitė, I. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. Х. Медведевайте. О гиперповерхности метрического пространства гиперплоских элементов I. Medviedevaitė. Apie metrinės hiperplokštuminių elementų erdvės hiperpaviršius